2021
DOI: 10.1101/2021.01.10.21249550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Metabolic Emergencies in Diabetes and COVID-19: a systematic review and meta-analysis of case reports

Abstract: BackgroundCOVID-19 is associated with DKA (Diabetic Ketoacidosis), HHS (Hyperglycaemic Hyperosmolar State) and EDKA (Euglycaemic DKA). High mortality has been observed in COVID-19-related diabetic ketoacidosis; however, evidence is scarce.MethodsA systematic literature review was conducted using EMBASE, PubMed/Medline, and Google Scholar from January to December 2020 to identify all case reports describing DKA, HHS, and EDKA, in COVID-19 patients. The Joanna Briggs Institute critical appraisal checklist for ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…Our findings are in keeping with a recent meta-analysis of 41 case reports carried out by our team, which yielded a mortality rate of 32.4% among 68 patients with known outcome [13]. We are totally aware that including a self-report in a meta-analysis can import a severe bias.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are in keeping with a recent meta-analysis of 41 case reports carried out by our team, which yielded a mortality rate of 32.4% among 68 patients with known outcome [13]. We are totally aware that including a self-report in a meta-analysis can import a severe bias.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, two small case series exhibited significantly lower mortality rates that range from 7.7% [8] to 12.9% [12]. Additionally, a few dozen of case reports concerning acute emergencies related to glucose metabolism in COVID-19 patients have been reported, all reviewed in a very recent meta-analysis [13].…”
Section: Text Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Observational studies (cross-sectional studies, cohort studies, case-control studies, case reports, case series 25 ) describing adult patients (>18 years old, independently of sex/gender) with both COVID19 (confirmed by nasopharyngeal swab or bronchoalveolar lavage PCR test 37 ) and any cerebrovascular disease. • Clinical trials (randomized, quasi-randomized or nonrandomized) describing adult patients (>18 years old, independently of sex/gender) with both COVID19 (confirmed by nasopharyngeal swab or bronchoalveolar lavage PCR test 37 ) and any cerebrovascular disease. • No specific diagnostic criteria for cerebrovascular disorders will be considered if the studies describe their population as presenting the condition, as previously reported 38 .…”
Section: Eligibility Criteria Inclusion Criteriamentioning
confidence: 99%
“…The hyperactivation of the cytokine cascade (cytokine storm), the viral breach in the lymphoid organs and the expression of spike protein's ligand, ACE2, by the lymphocytes comprise a suggested biological explanation towards the presence of lymphopenia [165]. Although the role of metabolism has been relatively unvisited in the subject, severe metabolic imbalances, such as metabolic acidosis, have been directly linked to COVID-19 clinical manifestations [166,167]. It has been demonstrated that elevations in serum lactic acid levels compromise T cell metabolism and function, leading to T cell reduction [168].…”
Section: Metabolomics In Post-covid Syndromementioning
confidence: 99%